Current Account Deficits, External Liabilities and Economic Policy - Pitchford, J. (IMF Working Papers; Working Paper ;, 1992)
This paper assesses the policy significance of foreign liabilities and the current account deficits that give rise to them. Current account imbalances are shown to have some capacity to indicate difficulties elsewhere in the economy, but are imperfect indicators and subject to potential misinterpretation. The paper concludes that successful pursuit of internal balance could be an important factor in stabilizing current account balances, but, beyond that, there seems no good reason for using macroeconomic policy to target the current account as such. However, there may be grounds for microeconomic action to remedy specifically identified problems.